Use of Almitrine and Inhaled Nitric Oxide in ARDS Due to COVID-19 - Laghlam, Driss; Rahoual, Ghilas; Malvy, Julien; Estagnasié, Philippe; Brusset, Alain; Squara, Pierre (Frontiers in Medicine, 2021)
Introduction. Severe SARS-COV-2 is manifested by an acute respiratory distress syndrome (ARDS) with intense inflammation and endothelial dysfunction leading to particularly severe hypoxemia. We hypothesized that an impaired hypoxic pulmonary vasoconstriction aggravates hypoxemia. The objective of the study was to test the effect of two pulmonary vasoactive drugs on patient oxygenation. Methods. Observational, single-centre, open-label study in one ICU of the Paris area, realised in April 2020. Eligible patients had COVID-19 and moderate to severe ARDS (PaO2/FiO2<200 mmHg) despite conventional protective ventilation. Exclusion criteria included pulmonary artery hypertension defined by a pulmonary artery systolic pressure (PAPs)>45 mmHg. The assessment of oxygenation was based on PaO2/FiO2 at 1) baseline, then after 2) 30 minutes of inhaled NO (iNO), 10 ppm alone, then 3) 30 minutes combination of iNO + almitrine infusion 8 g/kg/minutes, then 4) 30 minutes of almitrine infusion alone. Results. Among twenty patients requiring mechanical ventilation during the study period, twelve met the inclusion criteria. Baseline PaO2/FiO2 was 146±48 mmHg. When iNO was combined with almitrine, PaO2/FiO2 rose to 255±90 mmHg, (+80±49%, p=0.005), also after Almitrine alone: 238±98 mmHg (+67±75%, p=0.02), but not after iNO alone: 185 ± 73mmHg (+30±5%, p=0.49). No adverse events related to almitrine infusion or iNO was observed. Conclusion. Combining iNO and infused almitrine improved the short-term oxygenation in patients with COVID-19- related ARDS. This combination may be of interest when first-line therapies fail to restore adequate oxygenation. These findings argue for an impaired pulmonary hypoxic vasoconstriction in these patients.